2018
DOI: 10.1177/0049475518788474
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of displaced paediatric supracondylar fractures: a systematic review

Abstract: In low-income countries, where surgical expertise and resources are limited, displaced supracondylar fractures of the distal humerus are routinely managed with traction or closed reduction and casting. This is in contrast to high-income nations, where percutaneous K-wire fixation forms the mainstay of treatment. The aim of our study is to present the published evidence regarding the outcome of conservatively managed displaced supracondylar fractures in children. A systematic review of the literature was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Most of the research on the topic focuses on surgical treatment, which is not a widely available management option for children in LICs outside of large metropolitan areas with academic centres [4,11,12]. The closed reduction and percutaneous pinning procedures most commonly compared are especially inapplicable to many children in LICs because of limited availability of fluoroscopy in these settings [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research on the topic focuses on surgical treatment, which is not a widely available management option for children in LICs outside of large metropolitan areas with academic centres [4,11,12]. The closed reduction and percutaneous pinning procedures most commonly compared are especially inapplicable to many children in LICs because of limited availability of fluoroscopy in these settings [13].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, many surgeons in low-income countries, often hindered by lack of essential resources and training in operative techniques, may treat displaced supracondylar humerus fractures non-operatively-with traction, closed reduction with or without fluoroscopy, and splinting/casting [4]. This disparity in treatment may result in poor clinical and functional outcomes for children in low-and lower middle-income countries (LICs) given the concern that mal-reduced supracondylar humerus fractures can lead to angular deformity and restrictions of motion.…”
Section: Introductionmentioning
confidence: 99%
“…We note, though, that traction is occasionally used, and equivocal results comparing traction with percutaneous fixation have been reported. 15 This study has several limitations. As it is a retrospective study, data collected may not be entirely accurate, and it is not possible to be certain that all eligible patients were identified in each of the collaborating units.…”
Section: Discussionmentioning
confidence: 92%
“…SCHFs are common, but few studies have examined outcomes in low- and middle-income countries, where many patients are treated nonoperatively because of limited surgical capacity 19,25 . In our retrospective assessment of children with closed SCHFs treated nonoperatively at NKKDH in Malawi, we found that patients with Gartland type-II and III fractures had a significantly increased risk of clinical complications and functional impairment compared with patients with type-I fractures.…”
Section: Discussionmentioning
confidence: 99%